(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The environment provides a platform for every business enterprise to strive. Therefore, it is imperative that there should be accountability on the use of environment especially in financial terms. The impact of such financial accountability on the financial performance of enterprises is also of great concern. Hence, the study was aimed at assessing the impact of environmental cost accounting ontheprofitability of consumer goods companies in Nigeria. Two research questions were raised andanswered while two hypotheses were tested. The study covered a period of ten years (2013-2022). The design of the study was ex-post fact research design. Sixteen consumer goods companies whoseannual reports were published participated in the study. Annual reports were used as instrument for data collection. Pearson correlation and panel least square regression analysis were used to analyzethe study. The findings of the study revealed that environmental cost had a positive but weak impact on returns on equity and a negative impact on returns on assets of consumer goods companies in Nigeria